H2O2-mediated autophagy during ethanol metabolism - Chen, Cheng; Wang, Shijin; Yu, Linna; Müller, Johannes; Fortunato, Franco; Rausch, Vanessa; Mueller, Sebastian (Redox Biology, 2021)
Background - Alcoholic liver disease (ALD) is the most common liver disease worldwide and its underlying molecular mechanisms are still poorly understood. Moreover, conflicting data have been reported on potentially protective autophagy, the exact role of ethanol-metabolizing enzymes and ROS. - Methods - Expression of LC3B, CYP2E1, and NOX4 was studied in a mouse model of acute ethanol exposure by immunoblotting and immunohistochemistry. Autophagy was further studied in primary mouse hepatocytes and huh7 cells in response to ethanol and its major intermediator acetaldehyde. Experiments were carried out in cells overexpressing CYP2E1 and knock down of NOX4 using siRNA. The response to external H2O2 was studied by using the GOX/CAT system. Autophagic flux was monitored using the mRFP-GFP-LC3 plasmid, while rapamycin and chloroquine served as positive and negative controls. - Results - Acute ethanol exposure of mice over 24 h significantly induced autophagy as measured by LC3B expression but also induced the ROS-generating CYP2E1 and NOX4 enzymes. Notably, ethanol but not its downstream metabolite acetaldehyde induced autophagy in primary mouse hepatocytes. In contrast, autophagy could only be induced in huh7 cells in the presence of overexpressed CYP2E1. In addition, overexpression of NOX4 also significantly increased autophagy, which could be blocked by siRNA mediated knock down. The antioxidant N-acetylcysteine (NAC) also efficiently blocked CYP2E1-and NOX4-mediated induction of autophagy. Finally, specific and non-toxic production of H2O2 by the GOX/CAT system as evidenced by elevated peroxiredoxin (Prx-2) also induced LC3B which was efficiently blocked by NAC. H2O2 strongly increased the autophagic flux as measured by mRFP-GFP-LC3 plasmid. - Conclusion - We here provide evidence that short-term ethanol exposure induces autophagy in hepatocytes both in vivo and in vitro through the generation of ROS. These data suggest that suppression of autophagy by ethanol is most likely due to longer alcohol exposure during chronic alcohol consumption with the accumulation of e.g. misfolded proteins.